PENGARUH PROMOSI JABATAN, KOMPENSASI, DAN KINERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA TWIN PLAZA HOTEL JAKARTA - Fiman Maulana Romdoni; Mey Veronica Pohan (LPPM Universitas Asa Indonesia, 2015)
Purpose- The research is to findout the effect of promotion, compensation,performance against job satisfaction of the employee of Twin plaza Hotel Jakarta. Design/methology/approach- Findings- Compensation is more effective in achieveing the job satisfaction, eventhough promotion and performance are the basic to set up the compensation. Research Limitations- The object of research is limited to one company, and it is not applicable for the big company such state owned company. Practical implications- It is recommende to evaluate the existing compensation when the performance in declining stage to boost productivity and control over the employee.